Adopting New Technology in Coffe Plantation :The Role of Knowledge Sharing in Supply Chain Management - Andrey Satwika Yogaswara; Andre Suryaningprang; Disman Disman; Ratih Hurriyati (International Journal of Supply Chain Management, 2020)
The problem currently faced is that the ground coffee beans are dried and still found many defects, the defects are caused form sorting system, a good coffee system can increase sales of farmers businesses that initially only sold coffee beans without sorting with simple technology, but with the computerized method of sorting system and sales development will continue to increase with modern computer sorting standards than manual sorting and coffee beans become greenbean. in this study, the application of Computer Vision will be tested to facilitate a sorting process, a computer system with the help of a camera will introduce a type of coffee recognition system to Robusta and Arabica, this system is able to read the number of defects that exist in coffee, this system is able to be implemented and has more accuracy of 90%. coffee that has been sorted automatically will have a good quality and perfect shape of beans and will produce have unique aroma and will automatically increase the sale value. This system makes added value for coffee bean farmers, training on knowledge of the sorting system that uses computer applications and practices in running the system supports working farmers to work more efficiently and effectively and provide maximum results in accordance with market needs.